Efektivitas Penggunaan Media Audio Visual dalam Pembelajaran Pendidikan Pancasila dan Kewarganegaraan Materi Norma di SMP Negeri 6 Samarinda - Novadila Ramadhana; Wingkolatin Wingkolatin; Novita Majid (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
This research shows that the effectiveness of learning is measured by the success of the relationship between students and teachers to achieve learning goals. This study aims to determine the effectiveness of the use of audio visual media in learning Pancasila and Civics Education (PPKn) in class VII of SMP Negeri 6 Samarinda and its inhibiting factors. The research subjects involved Civics teachers, principals, and students using observation, interview, and documentation techniques. The results showed that the use of audio visual media had a positive impact on students' participation and involvement in learning. Although some students did not fully agree, overall audio visual media improved students' understanding. However, there are internal inhibiting factors such as students' limited knowledge and motivation, as well as external factors such as internet access problems, lack of technological infrastructure, and support from the environment that affect the effectiveness of using audio visual media in learning.